Building up a web-based e-lifestyle application - Guo, Linjing. (2013)
The trend of online shopping keeps growing. Various information on deal, coupon and promotion events are released every day by the respective business entities. The traditional way of promoting business was to put advertisement on company’s own website, in social network, on newspaper or TV. And for potential customers, they have no exact way to filter out those information they want, and have no way of getting the information in one place. NetLife develops a solution for both business companies and customers to get advertised information in one place.